Negative electrode material, preparation method thereof and lithium ion battery
By growing hard carbon in situ in artificial graphite, forming a mosaic structure, and using heterogeneous thermal expansion technology, the problem of artificial graphite volume expansion during the lithium-ion battery cycle is solved, and the characteristics of high capacity, low expansion and long cycle are achieved.
Patent Information
- Application Number
- CN202411956528.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In the prior art, artificial graphite will undergo large volume expansion during the circulation process of lithium-ion batteries, resulting in poor circulation performance and it is difficult to take into account both high capacity and long circulation.
By growing hard carbon in situ in artificial graphite to form a mosaic structure, the mass content of hard carbon is controlled between 5 wt% and 15 wt%, and artificial graphite is recombined with hard carbon by heterogeneous thermal expansion technology.
It improves the structural stability of artificial graphite, reduces volume expansion, and avoids side reactions caused by hard carbon high-active surfaces, so that the negative electrode material has the characteristics of low expansion and long cycles while maintaining high capacity and high kinetics.
Smart Images

Figure CN119786556A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have many advantages such as high voltage, high capacity, long cycle life, low self-discharge efficiency, and good safety performance. They are widely used in 3C / digital products, electric vehicles, energy storage, etc. The negative electrode material is an important component of lithium-ion batteries. The composition and structure of the negative electrode material have a decisive influence on the electrochemical performance of lithium-ion batteries.
[0003] At present, the carbon-based negative electrode materials of commercial lithium-ion batteries are mainly natural graphite and artificial graphite. Among them, artificial graphite has the characteristics of a wide range of raw material sources and fewer surface side reactions, but it is often difficult to take into account both high capacity and long cycle. The reason is that artificial graphite will undergo a large volume expansion during the cycle, which affects the cycle performance of artificial graphite. In the prior art, there are ways to reduce the expansion force of artificial graphite by secondary granulation or surface coating, but these methods will either deteriorate the capacity and compactness, or deteriorate the high temperature performance.
[0004] Therefore, it is necessary to provide a negative electrode material and a preparation method thereof that can achieve both high capacity and long cycle time. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a negative electrode material and a preparation method thereof and a lithium ion battery to improve the expansion problem of artificial graphite so that it can have the characteristics of high capacity and long cycle.
[0006] To achieve the above-mentioned object and other related objects, the present invention provides a negative electrode material in a first aspect, wherein the negative electrode material comprises artificial graphite and hard carbon, wherein the hard carbon is in-situ grown and embedded in the artificial graphite, and the mass content of the hard carbon in the negative electrode material is W HC 5wt%≤W HC ≤15wt%.
[0007] In one embodiment of the present invention, the powder compaction P1 of the negative electrode material at 80 MPa is 1.62≤P≤1.68 g / cm 3 , the powder compaction P2 at 200MPa is 1.68≤P2≤1.73g / cm 3 .
[0008] In one embodiment of the present invention, the particle size Dv50 of the negative electrode material is 7.5 μm to 10 μm.
[0009] A second aspect of the present invention provides a method for preparing a negative electrode material, the preparation method comprising the following steps:
[0010] Taking a portion of the graphite precursor and subjecting it to semi-calcination treatment and crushing and shaping treatment to obtain a first graphite precursor; taking another portion of the graphite precursor and subjecting it to crushing and shaping treatment to obtain a second graphite precursor;
[0011] Thermally shaping the first graphite precursor and the second graphite precursor, and respectively mixing a hard carbon precursor into the thermally shaped first graphite precursor and the second graphite precursor to disperse them uniformly, thereby obtaining a first composite precursor and a second composite precursor;
[0012] The first composite precursor and the second composite precursor are alternately filled into a grid-shaped crucible furnace in sequence and graphitized to obtain a negative electrode material having an artificial graphite-hard carbon in-situ composite.
[0013] In one embodiment of the present invention, the first graphite precursor and the second graphite precursor have the same mass, and the semi-calcination treatment is performed at a temperature of 600° C. to 900° C. for a time of 3 h to 5 h.
[0014] In one embodiment of the present invention, the graphite precursor is selected from coal-based needle coke, and the volatile content of the coal-based needle coke is greater than 10% and less than 15%;
[0015] And / or, the hard carbon precursor is selected from coal tar pitch quinoline insolubles, and the molecular weight of the coal tar pitch quinoline insolubles is 1800 to 2600.
[0016] In one embodiment of the present invention, the added amount of the hard carbon precursor accounts for 15% to 40% of the mass of the first graphite precursor or the second graphite precursor.
[0017] In one embodiment of the present invention, the temperature of the graphitization treatment is 2500°C to 2800°C.
[0018] In one embodiment of the present invention, the particle size distribution of the first graphite precursor and the second graphite precursor satisfies: Dv50 is 3 μm to 5 μm, (Dv90-Dv10) / Dv50≤1.2.
[0019] The present invention also provides a lithium ion battery, the lithium ion battery comprises a negative electrode plate, the negative electrode plate comprises any of the above-mentioned negative electrode materials or a negative electrode material prepared by any of the above-mentioned preparation methods.
[0020] The negative electrode material of the present invention comprises artificial graphite and hard carbon, and the hard carbon and the artificial graphite form an in-situ embedded structure. The hard carbon has a stable structure and a small volume change when lithium is embedded, which is beneficial to improving the structural stability of the artificial graphite and reducing the volume expansion of the artificial graphite. In addition, the hard carbon is embedded in the artificial graphite and is not exposed on the surface of the artificial graphite, thereby avoiding the side reactions caused by the high-activity surface of the hard carbon, so that the negative electrode material has the characteristics of high capacity and long cycle at the same time.
[0021] The present invention utilizes in-situ heterogeneous thermal expansion technology to in-situ composite artificial graphite with hard carbon, and utilizes the hard carbon embedded in the artificial graphite to improve its structural stability and improve the volume expansion problem. At the same time, it avoids the side reactions caused by the high active surface of the hard carbon, so that the negative electrode material has the characteristics of low expansion and long cycle while maintaining high capacity and high kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A schematic diagram of the structure of the negative electrode material of the present invention in one embodiment;
[0024] Figure 2 FIG. 1 is a flow chart of a method for preparing a negative electrode material according to an embodiment of the present invention.
[0025] Figure Number:
[0026] 10. Negative electrode material; 11. Artificial graphite; 12. Hard carbon. DETAILED DESCRIPTION
[0027] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and the features in the embodiments can be combined with each other without conflict. The test methods for which specific conditions are not specified in the following embodiments are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0029] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0030] The definitions of the professional terms used in this article are as follows:
[0031] Dv10 represents the particle size corresponding to the cumulative volume distribution reaching 10% in the particle size distribution;
[0032] Dv50 represents the particle size corresponding to 90% of the cumulative volume distribution in the particle size distribution;
[0033] Dv90 represents the particle size corresponding to the cumulative volume distribution reaching 90% in the particle size distribution.
[0034] See also Figure 1 In a first aspect, the present invention provides a negative electrode material 10, which includes artificial graphite 11 and hard carbon 12, wherein the hard carbon 12 is in-situ grown and embedded in the artificial graphite 11. In one embodiment, the negative electrode material is a garnet structure, wherein the artificial graphite 11 is the outer shell and inner membrane of the garnet structure, and the hard carbon 12 is a pomegranate seed embedded in the outer shell. The hard carbon crystals and artificial graphite crystals of this structure are chemically bonded, which has little effect on the compaction of the material, and the hard carbon is not exposed on the surface of the material, thereby avoiding the side reactions caused by the high-activity surface of the hard carbon and improving the long-cycle performance of the material.
[0035] In addition, the interlayer spacing d1 of the hard carbon 12 is greater than the interlayer spacing d2 of the artificial graphite 11. The combination of the hard carbon 12 and the artificial graphite 11 can increase the lithium ion channel, improve the lithium ion diffusion and enhance its rate performance. However, if the content of the hard carbon 12 in the negative electrode material 10 is too high, the energy density of the lithium ion battery will decrease, and the occurrence of side reactions during the cycle will cause its cycle life to decrease. In the present invention, the mass content of the hard carbon 12 in the negative electrode material 10 is W HC 5wt%≤W HC ≤15wt%. As an example, the mass content of the hard carbon 12 in the negative electrode material 10 is W HC It can be 5wt%, 10wt% or 15wt% and so on.
[0036] In one embodiment, the powder compaction P1 of the negative electrode material 10 at 80 MPa is 1.62≤P1≤1.68 g / cm 3 , the powder compaction P2 at 200Mpa is 1.68≤P2≤1.73g / cm 3 . Powder compaction indicates the total mass of the powder sample per unit volume, which refers to the process in which the particles of the powder material are rearranged and the voids are reduced under the action of external pressure, thereby increasing its density. Therefore, under different external pressures, the negative electrode material 10 presents different compaction values. The above 80MPa corresponds to the preparation conditions of the negative electrode sheet of the battery, that is, the use conditions of the negative electrode material 10, and 200MPa corresponds to the limit conditions of the negative electrode material 10. The powder compaction of the negative electrode material 10 is closely related to the compaction density of the negative electrode sheet. The greater the powder compaction, the greater the compaction density of the negative electrode sheet, and the compaction density of the negative electrode sheet affects the performance of the battery. If the powder compaction of the negative electrode material 10 is too high, the compaction density of the pole piece will be too high, the gap between the particles will become smaller, the wettability of the pole piece will become worse and worse, and the insertion / extraction of lithium ions will become difficult, which will increase the polarization of the battery; if the powder compaction of the negative electrode material 10 is too low, the compaction density of the pole piece will be too low. Although the wettability of the pole piece can be improved, it will cause the contact performance between the negative electrode particles and between the negative electrode particles and the current collector to deteriorate, which will lead to a decrease in the electronic conductivity of the negative electrode. Therefore, the negative electrode material has a suitable powder compaction, which means that the negative electrode pole piece has a suitable compaction density. In some embodiments, the powder compaction P of the negative electrode material 10 at 80Mpa can be 1.62g / cm 3 , 1.65g / cm 3 or 1.68 g / cm 3 The powder compaction P2 of the negative electrode material 10 at 200 MPa can be 1.68 g / cm 3 , 1.70g / cm 3 or 1.73 g / cm 3 The powder compaction of the negative electrode material 10 of the present invention at 80 MPa is close to that at 200 MPa, indicating that the structural stability of the negative electrode material is good.
[0037] In one embodiment, the particle size Dv50 of the negative electrode material 10 is 7.5 μm to 10 μm. Dv50 represents the particle size corresponding to when the cumulative volume distribution reaches 50% in the particle size distribution. For example, the particle size Dv50 of the negative electrode material 10 can be 7.5 μm, 9 μm or 10 μm, etc.
[0038] The second aspect of the present invention provides a method for preparing a negative electrode material. The negative electrode material prepared by the preparation method is an artificial graphite-hard carbon in-situ embedded structure. The structure of the negative electrode material with this structure is more stable and can effectively improve the volume expansion during the battery cycle, so that the negative electrode material has the characteristics of high capacity, low expansion and long cycle.
[0039] See also Figure 2 The method for preparing the negative electrode material comprises at least the following steps:
[0040] S1, taking part of the graphite precursor for semi-calcination and crushing and shaping to obtain a first graphite precursor; taking another part of the graphite precursor for crushing and shaping to obtain a second graphite precursor;
[0041] S2, thermally shaping the first graphite precursor and the second graphite precursor, and respectively mixing the hard carbon precursor into the first graphite precursor and the second graphite precursor after thermal shaping, and dispersing them evenly to obtain a first composite precursor and a second composite precursor;
[0042] S3, alternately filling the first composite precursor and the second composite precursor into a grid-shaped crucible furnace in sequence, and performing graphitization treatment to obtain a negative electrode material having an artificial graphite-hard carbon in-situ composite.
[0043] Specifically, the graphite precursor in step S1 can be any raw material that can be used to prepare artificial graphite in the art, including but not limited to coal-based needle coke (asphalt coke made from coal-based residual oil), etc. In one embodiment, the graphite precursor is coal-based needle coke, and the volatile content (weight percentage) of the coal-based needle coke is greater than 10% and less than 15%. For example, the volatile content of coal-based needle coke can be 11%, 12%, 13%, 14%, etc. Selecting coal-based needle coke with a high volatile content as the raw material of artificial graphite is convenient for controlling the heterogeneous thermal expansion during the graphitization process, thereby obtaining a graphite-hard carbon in-situ composite material with a mosaic structure, and selecting coal-based needle coke as the raw material can also ensure the high capacity of artificial graphite. It should be noted that: volatiles refer to liquid (vapor state) and gaseous products with smaller molecular weights that are decomposed by heat when the sample is isolated from air and heated. These products are called volatiles. The fraction of volatiles in the mass of the coal sample is called the volatile yield or simply volatiles. The volatile content of coal-based needle coke can be tested by methods known in the art, for example, by referring to SH / T 0026-1990.
[0044] Step S1 is to take two portions of graphite precursors and treat them separately. The first portion of graphite precursor is first semi-calcined and then crushed and shaped to obtain the first graphite precursor; the second portion of graphite precursor is directly crushed and shaped to obtain the second graphite precursor. Among them, the semi-calcined treatment is to heat-treat the graphite precursor at a certain temperature to remove some organic matter and impurities in the graphite precursor and improve the purity of the material (also known as semi-purification). The temperature of the semi-calcined treatment is related to the material of the selected graphite precursor. In the present invention, the graphite precursor is coal-based needle coke, and the temperature of the semi-calcined treatment is 600℃~800℃, which can be specifically listed as 600℃, 700℃ or 800℃. The time of the semi-calcined treatment has little effect on the treatment effect, and no specific restrictions are made here. It can be set according to actual production. For example, the time of the semi-calcined treatment is 3~5h, which can be specifically 3h, 4h or 5h. The first graphite precursor is semi-calcined, and the second graphite precursor is not semi-calcined, so that the volatile components in the first and second graphite precursors remain different, and different thermal expansion effects are maintained during the subsequent graphitization process, thereby achieving heterogeneous thermal expansion. Preferably, the first graphite precursor and the second graphite precursor are equal in amount.
[0045] The purpose of the crushing and shaping treatment is to crush the large pieces of graphite precursor into small particles to ensure the uniformity of the subsequent preparation of the material. In this step, the coal-based needle coke can be crushed using equipment and methods known in the art, such as air flow mills, mechanical mills or roller mills. The crushing process often produces a large number of too small particles, and sometimes there are too large particles. Therefore, after crushing, classification treatment can be carried out according to demand to remove the too small particles and too large particles in the crushed powder. After classification treatment, a granular product with a good particle size distribution can be obtained to facilitate subsequent processes. Classification treatment can be carried out using equipment and methods known in the art, such as a grading screen, a gravity classifier, a centrifugal classifier, etc.
[0046] The particle size Dv50 of the first graphite precursor and the second graphite precursor obtained in step S1 is 3 to 5 μm, for example, 3 μm, 4 μm or 5 μm, etc. The particle size distribution width (Dv90-Dv10) / Dv50≤1.2, for example, 1.1, 1.0, 0.8, 0.5, etc. The particle size distribution width (Dv90-Dv10) / Dv50 is an indicator for measuring the uniformity of particle size. The larger the particle size distribution width, the wider the particle size distribution, that is, the greater the difference between large particles and small particles; the closer the particle size distribution width is to 0, the more uniform the particle size and the higher the size consistency.
[0047] Step S2 is to perform heat shaping treatment on the first graphite precursor and the second graphite precursor obtained in step S1, respectively, to grind the edges and corners of the particle product obtained in step S1, improve its sphericity, and further improve its tap density. The heat shaping treatment can be performed using a shaping machine or other shaping equipment. The temperature of the heat shaping is 400°C to 600°C, for example, 400°C, 500°C or 600°C. Exemplarily, the frequency of the heat shaping is 80Hz, and the time of the heat shaping is 6h. After heat shaping, the tap density of the graphite precursor is greater than 0.9g / cm 3 Afterwards, the fines are removed and the powder precursor is collected.
[0048] Then, a hard carbon precursor is mixed into the first graphite precursor and the second graphite precursor respectively, and dispersed evenly to obtain a first composite precursor and a second composite precursor. The hard carbon precursor can be any carbon-containing material that can prepare hard carbon, such as coal tar quinoline insolubles, phenolic resin, etc. In one embodiment, the hard carbon precursor is coal tar quinoline insolubles.
[0049] The amount and molecular weight of the hard carbon precursor added will affect the hard carbon content in the final product. In some embodiments, the amount of the hard carbon precursor added to the first graphite precursor accounts for 15% to 40% of the mass of the first graphite precursor, and the amount of the hard carbon precursor added to the second graphite precursor accounts for 15% to 40% of the mass of the second graphite precursor. To ensure the uniformity of the final product, the hard carbon precursor addition ratio in the first graphite precursor and the second graphite precursor is the same, for example, it can be 15%, 20%, 25%, 30%, 35% or 40%, etc. In some embodiments, the molecular weight of the hard carbon precursor is 1800 to 2600, optionally, the molecular weight of the hard carbon precursor is 1800, 2000, 2300 or 2600, etc.
[0050] Step S3 is to alternately fill the first composite precursor and the second composite precursor obtained in step S2 into a grid-mounted crucible furnace, and then perform high-temperature graphitization treatment to obtain an in-situ grown artificial graphite-hard carbon composite material with a mosaic structure.
[0051] In one embodiment, step S3 specifically includes: firstly, a 400kg cylindrical crucible furnace (60cm in diameter) is divided into 5*5cm interval areas in the longitudinal direction by a prefabricated grid plate, and then the first composite precursor and the second composite precursor prepared in step S2 are sequentially filled into the interval areas, and then high-temperature graphitization treatment is performed. Since the graphite precursor in the first composite precursor is semi-calcined in step S1, and the graphite precursor in the second composite precursor is not semi-calcined, the volatile content of the two is different. Therefore, the expansion of the two is also different at high temperature, and the expansion size is ranked as follows: hard carbon precursor>unpurified graphite precursor (second graphite precursor)>semi-purified graphite precursor (first graphite precursor). During the graphitization process, the hard carbon is embedded in the artificial graphite by using heterogeneous expansion to form a garnet mosaic structure. It should be noted that the shape and size of the crucible and the size of the interval area in this step are not specifically limited, and it is only necessary to ensure that the first composite precursor and the second composite precursor are alternately filled in sequence. In other embodiments, crucible furnaces of other sizes may also be used, such as a crucible with a diameter of 80 cm, and the size of each spacing area is not limited to 5*5 cm, but may also be 3*3 cm, 1*1 cm or 10*10 cm, etc.
[0052] The graphitization temperature in step S3 is 2500°C to 2800°C, for example, 2500°C, 2600°C, 2700°C or 2800°C, etc. If the graphitization temperature is too high, the hard carbon precursor will be highly graphitized and the hard carbon content in the negative electrode material will be too low. If the graphitization temperature is too low, the formation of artificial graphite will be affected, thereby affecting the performance of the negative electrode material. The time of graphitization treatment can be carried out according to the conventional graphitization time in the art. In some embodiments, the time of graphitization treatment is 12 to 18 hours, for example, 12 hours, 15 hours or 18 hours, etc.
[0053] After step S3 is completed, the graphitized product is collected and shaped and subdivided to obtain a negative electrode material with a particle size Dv50 of 7.5 to 10 μm.
[0054] The third aspect of the present invention provides a lithium ion battery, which includes a non-aqueous electrolyte lithium battery, a solid lithium battery, etc. Taking a non-aqueous electrolyte lithium battery as an example, the lithium ion battery includes a negative electrode sheet, a positive electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet includes the above-mentioned negative electrode material of the present invention or the negative electrode material prepared by the above-mentioned preparation method.
[0055] Specifically, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector. The negative electrode current collector may be made of conventional materials in the art, such as copper foil, carbon-coated copper foil, etc. The negative electrode active material layer may be disposed on the surface of one side of the negative electrode current collector, or on the surface of both sides. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder, wherein the negative electrode active material is selected from materials capable of embedding and de-embedding lithium ions, and the negative electrode active material in the present invention is the above-prepared artificial graphite-hard carbon in-situ embedded negative electrode material. The negative electrode conductive agent can improve the electronic conductivity, and plays a role in collecting microcurrents between the negative electrode active materials and between the negative electrode active materials and the negative electrode current collector, so as to reduce the contact resistance of the battery and accelerate the movement rate of electrons. In some embodiments, the negative electrode conductive agent includes at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotubes, and graphene. Optionally, the negative electrode conductive agent is conductive carbon black; or, a combination of carbon fiber and conductive carbon black; or, a combination of carbon nanotubes and graphene, and the like. The binder is used to bond the negative electrode active material and the negative electrode conductor, and provide a certain bonding force for the negative electrode active material layer to bond it to the negative electrode current collector. As an example, the negative electrode binder is selected from at least one of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), styrene-acrylate, and acrylic copolymers. For example, the negative electrode binder is polyvinylidene fluoride, or a combination of styrene butadiene rubber and carboxymethyl cellulose, etc. The ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder can refer to the conventional settings in the art.
[0056] The preparation process of the negative electrode sheet is exemplified as follows: first, the negative electrode active material, the negative electrode conductive agent and the negative electrode binder are mixed and stirred in a solvent such as deionized water according to a certain ratio to form a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode collector. After drying, rolling, cutting and other processes, the negative electrode sheet is obtained.
[0057] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector may be made of conventional materials in the art, such as aluminum foil, carbon-coated aluminum foil, etc. The positive electrode active material layer may be disposed on the surface of one side of the positive electrode current collector, or on the surface of both sides. The positive electrode active material layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder, wherein the positive electrode active material may be selected from any positive electrode material suitable for lithium-ion batteries, that is, compounds that can reversibly embed and deintercalate lithium ions may be used. As an example, the positive electrode active material may be a ternary material, such as a nickel-cobalt-manganese ternary material (NCM), a nickel-cobalt-aluminum ternary material (NCA), etc., and the iron-lithium positive electrode material may be, for example, lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), etc., and may also be a traditional material such as lithium cobalt oxide, lithium manganese oxide, etc. These materials may be used alone or in combination. The positive electrode binder is, for example, any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene-butadiene rubber (SBR), etc. The positive electrode conductive agent includes, but is not limited to, at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotubes, and graphene. Optionally, the conductive agent is conductive carbon black; or, a combination of carbon fiber and conductive carbon black; or, a combination of carbon nanotubes and graphene, etc. The ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder can refer to the conventional settings in the art.
[0058] The preparation process of the positive electrode sheet is exemplified as follows: first, the positive electrode active material, the positive electrode conductor and the positive electrode binder are mixed and stirred in a solvent such as N-methylpyrrolidone (NMP) in a certain ratio to form a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector. After drying, rolling, cutting and other processes, the positive electrode sheet is obtained.
[0059] The diaphragm is set between the positive electrode and the negative electrode to separate the positive electrode and the negative electrode to prevent short circuit inside the battery, and at the same time allow lithium ions to pass through and move between the positive and negative electrodes to realize the battery's charge and discharge process. The diaphragm can be made of porous materials such as polyethylene film (PE), polypropylene film (PP), glass fiber film or composite film. The thickness of the diaphragm is 9 to 18μm, the air permeability is 180s / 100mL to 380s / 100mL; the porosity is 30% to 50%.
[0060] The lithium-ion battery also includes an electrolyte, which plays a role in conducting lithium ions during the battery charge and discharge process. The electrolyte includes an organic solvent and a lithium salt, and the lithium salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate phosphate) (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP). Further, the lithium salt is selected from lithium hexafluorophosphate with better comprehensive performance or a combination of lithium hexafluorophosphate and other lithium salts, such as a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. The organic solvent may be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC). The electrolyte may also include functional additives such as fluoroethylene carbonate (FEC), propenyl-1,3-sultone (PST), tetravinylsilane (TVSI), vinylene carbonate (VC), and diethylene sulfate (DTD), which may be added according to actual production needs.
[0061] Battery assembly: Place the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, with the separator placed between the positive and negative electrode sheets to isolate them, and obtain a bare cell by winding or stacking. Put the bare cell into the battery shell, and obtain a lithium-ion battery after assembly, injection, formation, and capacity division.
[0062] In other embodiments, the lithium-ion battery may also be a solid-state lithium-ion battery. The electrolyte of the solid-state lithium-ion battery is solid. Common solid-state electrolytes are oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes, etc., which are not elaborated here. Those skilled in the art can make a selection according to actual production needs.
[0063] It should be noted that the structures not described in detail in the above lithium-ion battery can be configured with reference to the prior art and will not be described in detail here.
[0064] The lithium-ion battery of the present invention can be used in the form of a single cell, a battery module or a battery pack for electronic devices to power them. Electronic devices include but are not limited to mobile phones, tablets, laptops, electric toys, battery cars, new energy vehicles, ships, spacecraft, etc. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles and spacecraft, etc. New energy vehicles can be pure electric vehicles, hybrid vehicles or extended-range vehicles, etc.
[0065] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0066] Example 1
[0067] This embodiment provides a negative electrode material, which includes artificial graphite and hard carbon, wherein the hard carbon and the artificial graphite are in-situ composited to form a garnet mosaic structure, and the mass percentage of the hard carbon in the negative electrode material is W HC The negative electrode material has a powder compaction P1 of 1.65 g / cm2 at 80 MPa. 3 The powder compaction at 200 MPa is 1.70 g / cm 3 ; The Dv50 of the negative electrode material is 8.1μm.
[0068] This embodiment also provides a method for preparing the above-mentioned negative electrode material, comprising the following steps:
[0069] Step 1: Divide the high volatile matter (>10% and <15%) coal-based needle coke into two equal parts, A and B. The coal-based needle coke of part A is crushed into single particles of 3 to 5 μm after semi-calcination at 800°C, and the particle size distribution width (Dv90-Dv10) / Dv50 is controlled within 1.2, which is recorded as the first graphite precursor; the coal-based needle coke of part B is crushed into single particles of 3 to 5 μm, and the particle size distribution width (Dv90-Dv10) / Dv50 is controlled within 1.2, which is recorded as the second graphite precursor;
[0070] Step 2: subject the first graphite precursor and the second graphite precursor to high-frequency shaping at 500°C for 6 hours at 80 Hz, respectively, so that the tap density is greater than 0.9 g / cm 3 , removing excess fine powder and collecting; then respectively mixing 30wt% of coal tar quinoline insoluble matter (particle size <1μm) with a molecular weight of 2000 into the first graphite precursor and the second graphite precursor and dispersing them evenly to obtain a first composite precursor and a second composite precursor;
[0071] Step 3: Divide a 400 kg cylindrical crucible furnace (60 cm in diameter) into 5*5 cm interval areas in the longitudinal direction with a prefabricated grid plate, fill the first composite precursor and the second composite precursor into the interval areas in sequence, and then perform high-temperature graphitization at a graphitization temperature of 2500° C. for 15 h;
[0072] Step 4: Collect the above graphitized products, and perform shaping and subdivision treatment to obtain an artificial graphite-hard carbon in-situ composite negative electrode material with a particle size Dv50 of 8.1 μm.
[0073] Referring to Table 1, the present invention further provides Examples 2 to 4 and Comparative Examples 1 to 6.
[0074] Example 2
[0075] The difference between this embodiment and embodiment 1 is that the mass percentage of hard carbon in the negative electrode material is W HC The powder compaction P1 of the negative electrode material at 80 MPa is 1.62 g / cm 3 The powder compaction at 200 MPa is 1.68 g / cm 3 ; The Dv50 of the negative electrode material is 9.8μm.
[0076] In step 2 of the preparation method, the mass of the coal tar pitch quinoline insoluble matter added to the first graphite precursor and the second graphite precursor accounts for 40% of the mass of the first graphite precursor and the second graphite precursor respectively.
[0077] Example 3
[0078] The difference between this embodiment and embodiment 1 is that the mass percentage of hard carbon in the negative electrode material is W HC The powder compaction P1 of the negative electrode material at 80 MPa is 1.68 g / cm 3 The powder compaction at 200 MPa is 1.73 g / cm 3 ; The Dv50 of the negative electrode material is 7.5μm.
[0079] In step 2 of the preparation method, the mass of the coal tar quinoline insoluble matter added to the first graphite precursor and the second graphite precursor accounts for 15% of the mass of the first graphite precursor and the second graphite precursor respectively.
[0080] Example 4
[0081] The difference between this embodiment and embodiment 1 is that the mass percentage of hard carbon in the negative electrode material is W HC The powder compaction P1 of the negative electrode material at 80 MPa is 1.64 g / cm 3The powder compaction at 200 MPa is 1.68 g / cm 3 ; The Dv50 of the negative electrode material is 8.5μm.
[0082] The graphitization temperature in step three of the preparation method is 2800°C.
[0083] Comparative Example 1
[0084] This comparative example uses commercially available artificial graphite, whose powder compaction P1 at 80 MPa is 1.62 g / cm 3 The powder compaction at 200 MPa is 1.78 g / cm 3 ; The Dv50 of the negative electrode material is 9.5μm.
[0085] Comparative Example 2
[0086] The difference between this comparative example and Example 1 is that the mass percentage of hard carbon in the negative electrode material is W HC The powder compaction P1 of the negative electrode material at 80 MPa is 1.60 g / cm 3 The powder compaction at 200 MPa is 1.66 g / cm 3 ; The Dv50 of the negative electrode material is 10.5μm.
[0087] In step 2 of the preparation method, the mass of the coal tar pitch quinoline insoluble matter added to the first graphite precursor and the second graphite precursor accounts for 50% of the mass of the first graphite precursor and the second graphite precursor respectively.
[0088] Comparative Example 3
[0089] The difference between this comparative example and Example 1 is that the hard carbon and artificial graphite in the negative electrode material are simply physically mixed, and the powder compaction P1 of the negative electrode material at 80 MPa is 1.50 g / cm 3 The powder compaction at 200 MPa is 1.62 g / cm 3 ; The Dv50 of the negative electrode material is 9.8μm.
[0090] Preparation method: artificial graphite and hard carbon are physically mixed.
[0091] Comparative Example 4
[0092] The difference between this comparative example and Example 1 is that the mass percentage of hard carbon in the negative electrode material is W HC The powder compaction P1 of the negative electrode material at 80 MPa is 1.63 g / cm 3 The powder compaction at 200 MPa is 1.75 g / cm 3 ; The Dv50 of the negative electrode material is 7.1μm.
[0093] In step 2 of the preparation method, the mass of the coal tar pitch quinoline insoluble matter added to the first graphite precursor and the second graphite precursor accounts for 11% of the mass of the first graphite precursor and the second graphite precursor, respectively.
[0094] Comparative Example 5
[0095] The difference between this comparative example and Example 1 is that the mass percentage of hard carbon in the negative electrode material is W HC The powder compaction P1 of the negative electrode material at 80 MPa is 1.60 g / cm 3 The powder compaction at 200 MPa is 1.72 g / cm 3 ; The Dv50 of the negative electrode material is 8.5μm.
[0096] In step 1 of the preparation method, the temperature for semi-calcining the first graphite precursor is 1200°C.
[0097] Comparative Example 6
[0098] The difference between this comparative example and Example 1 is that the mass percentage of hard carbon in the negative electrode material is W HC The powder compaction P1 of the negative electrode material at 80 MPa is 1.67 g / cm 3 The powder compaction at 200 MPa is 1.79 g / cm 3 ; The Dv50 of the negative electrode material is 8.0μm.
[0099] The graphitization temperature in step three of the preparation method is 3000°C.
[0100] Table 1: Parameter characteristics and preparation method parameters of negative electrode materials of Examples 1 to 4 and Comparative Examples 1-6
[0101]
[0102]
[0103]
[0104] The powder compaction test of the negative electrode material in Table 1 refers to GB / T24533-2019; the test of the hard carbon content in the negative electrode material first refers to GB / T 24533-2019 to measure the d(002) of the negative electrode material. The negative electrode material is composed of pure graphite material (d(002) is 0.34nm) and hard carbon material (d(002) is 0.37nm). The formula d(002) measured = 0.34×graphite content + 0.37×hard carbon content (1-graphite content) can be used to calculate the hard carbon content and graphite content in the negative electrode material.
[0105] In order to verify the performance of the negative electrode material of the present invention, the inventors applied the negative electrode materials of Examples 1-4 and Comparative Examples 1-6 in lithium ion batteries, and performed performance tests on each lithium ion battery. The composition and test method of the lithium ion battery are as follows. The test results are shown in Table 2.
[0106] The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet, the separator and the negative electrode sheet are wound to obtain a battery cell, which is then packaged in a packaging shell and injected with an electrolyte to obtain a soft-pack battery.
[0107] Among them, the preparation of the negative electrode sheet: the negative electrode material obtained in the embodiment or the comparative example, the conductive agent (SP), the binder (PAA and SBR, the mass ratio of the two is 1.3:0.5) and the thickener carboxymethyl cellulose (CMC) are mixed in a mass ratio of 97.2:0.5:1.8:0.5 (a total of 100 parts by mass), and 82 parts by mass of deionized water are added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the copper foil; and then after drying, rolling, cutting and other processes, a negative electrode sheet is prepared.
[0108] Preparation of positive electrode sheet: The positive electrode active material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), PVDF and SP are mixed in a mass ratio of 97:1.8:1.2 (a total of 100 parts by mass), and 82 parts by mass of NMP are added to obtain a positive electrode slurry; the obtained positive electrode slurry is coated on an aluminum foil, dried, and rolled to obtain.
[0109] Diaphragm: Polyethylene film is used, the thickness of the diaphragm is 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; the porosity of the diaphragm is 40%.
[0110] The electrolyte used was a commercial electrolyte (manufacturer: Xinya Shanshan New Materials Technology (Quzhou) Co., Ltd., model: E3).
[0111] Battery performance test method
[0112] (1) First effect and discharge capacity
[0113] At 25°C, the battery was first activated by charging and discharging at 0.1C for one cycle, and then the lithium-ion battery obtained after the activation was connected to a blue electric charge and discharge tester for the first long cycle charge and discharge, and its charging capacity and discharge capacity were measured. The operating voltage range of the battery test was 2.8V (discharge cut-off voltage) to 4.35V (charge cut-off voltage), and the test rate was 0.3C.
[0114] First efficiency = first discharge capacity / first charge capacity × 100%
[0115] (2) Fast charging time
[0116] The battery cell is directly charged to 8% SOC with a current of 0.33C, and then according to the actual measured three-electrode window test of the battery cell, the charging windows of 10%, 20%, 30%, 40%, 50%, 60%, 70% and 80% are C1, C2, C3, C4, C5, C6, C7 and C8 respectively. The battery cell is charged gradually to 80%, that is, 8%-10% is charged with C1, 10% to 20% is charged with C2, and so on. The charging time from 8% to 80% SOC is recorded as the measure of fast charging capability. The calculation formula is T = (0.02 / C1+0.1 / C2+0.1 / C3+0.1 / C4+0.1 / C5+0.1 / C6+0.1 / C7+0.1 / C8)×60.
[0117] (3)Number of cycles at room temperature
[0118] At 25°C, first charge and discharge the battery for one cycle at 0.1C to activate it. Connect the activated lithium-ion battery prepared above to a blue electric charge and discharge tester, and then perform long-term cycling at a rate of 2C until the ratio of the capacity of the nth cycle to the capacity of the first cycle of 2C is less than 80%, and the capacity retention rate of the n-1th cycle is defined as 80%. The number of cycles is recorded as n-1, and the test is stopped.
[0119] (4) Storage days
[0120] At 25°C, the capacity is fixed with a current of 0.33C and recorded as C0. The battery cells are then stored at a high temperature of 60°C. After that, the battery cells are taken out every 7 days and the capacity is tested at room temperature and recorded as C1, C2…Cn. The number of days corresponding to the first time Cn is less than or equal to 80% of C0 is defined as the storage time.
[0121] Table 2: Performance of assembled batteries of Examples 1-4 and Comparative Examples 1-6
[0122]
[0123]
[0124] It can be seen from Table 1-Table 2 that the negative electrode materials of Examples 1-4 of the present invention have a garnet mosaic structure, and when applied to lithium-ion batteries, they still have good power performance when the cycle capacity is greater than 6000 cycles. Compared with commercially available artificial graphite (Comparative Example 1), the fast charging capacity and cycle performance are significantly improved; compared with the physical mixture of artificial graphite and hard carbon (Comparative Example 3), the fast charging capacity, cycle performance and storage performance are significantly improved.
[0125] By comparing the test results of Examples 1-3 with Comparative Examples 2 and 4, it can be seen that when the hard carbon content is within the range of 5-15wt%, the various properties of the negative electrode material are better than those outside this range. Too high or too low hard carbon content is detrimental to the cycle performance of the negative electrode material.
[0126] From the test results of Comparative Examples 1-3 and Comparative Examples 5-6, it can be seen that: the temperature of the semi-calcination treatment and the temperature of the graphitization treatment will affect the performance of the negative electrode material. If the temperature of the semi-calcination treatment is too high, the expansion of the first graphite precursor and the second graphite precursor will be similar, and the hard carbon and artificial graphite cannot be effectively compounded in situ, affecting the structure of the negative electrode material and thus affecting its performance; if the temperature of the graphitization treatment is too high, it will affect the hard carbon content in the negative electrode material, thereby affecting the powder compaction of the negative electrode material and the comprehensive performance of the negative electrode material.
[0127] The negative electrode material of the present invention includes artificial graphite and hard carbon, and the hard carbon and the artificial graphite form an in-situ embedded structure. The hard carbon has a stable structure, and its volume change is small when lithium is inserted. In addition, the hard carbon is embedded in the artificial graphite and is not exposed on the surface of the artificial graphite, thereby avoiding the side reactions caused by the high-activity surface of the hard carbon. The present invention utilizes the in-situ heterogeneous thermal expansion technology to in-situ compound the artificial graphite with the hard carbon, and utilizes the hard carbon embedded in the artificial graphite to improve its structural stability and improve the volume expansion problem. At the same time, it avoids the side reactions caused by the high-activity surface of the hard carbon, so that the negative electrode material has the characteristics of low expansion and long cycle while maintaining high capacity and high dynamics. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance.
[0128] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A negative electrode material, characterized in that: include: Artificial graphite and hard carbon, the hard carbon is in-situ grown and embedded in the artificial graphite, and the mass content of the hard carbon in the negative electrode material is W HC 5wt%≤W HC ≤15wt%.
2. The negative electrode material according to claim 1, characterized in that The powder compaction P1 of the negative electrode material at 80 MPa is 1.62≤P≤1.68 g / cm 3 , the powder compaction P2 at 200MPa is 1.68≤P2≤1.73g / cm 3 .
3. The negative electrode material according to claim 1, characterized in that The particle size Dv50 of the negative electrode material is 7.5 μm to 10 μm.
4. A method for preparing the negative electrode material according to claim 1, characterized in that: The following steps are involved: Taking part of the graphite precursor for semi-calcination and crushing and shaping to obtain a first graphite precursor; Taking another portion of the graphite precursor and performing crushing and shaping treatment to obtain a second graphite precursor; Thermally shaping the first graphite precursor and the second graphite precursor, and respectively mixing a hard carbon precursor into the thermally shaped first graphite precursor and the second graphite precursor to disperse them uniformly, thereby obtaining a first composite precursor and a second composite precursor; The first composite precursor and the second composite precursor are alternately filled into a grid-shaped crucible furnace in sequence and graphitized to obtain a negative electrode material having an artificial graphite-hard carbon in-situ composite.
5. The method for preparing the negative electrode material according to claim 4, characterized in that: The first graphite precursor and the second graphite precursor have the same mass, and the semi-calcination treatment is performed at a temperature of 600° C. to 900° C. for a time of 3 h to 5 h.
6. The method for preparing the negative electrode material according to claim 4, characterized in that: The graphite precursor is selected from coal-based needle coke, and the volatile content of the coal-based needle coke is greater than 10% and less than 15%; And / or, the hard carbon precursor is selected from coal tar pitch quinoline insolubles, and the molecular weight of the coal tar pitch quinoline insolubles is 1800 to 2600.
7. The method for preparing the negative electrode material according to claim 4, characterized in that: The added amount of the hard carbon precursor accounts for 15% to 40% of the mass of the first graphite precursor or the second graphite precursor.
8. The method for preparing the negative electrode material according to claim 4, characterized in that: The temperature of the graphitization treatment is 2500°C to 2800°C.
9. The method for preparing the negative electrode material according to claim 4, characterized in that: The particle size distribution of the first graphite precursor and the second graphite precursor satisfies: Dv50 is 3 μm to 5 μm, (Dv90-Dv10) / Dv50≤1.
2.
10. A lithium ion battery, characterized in that: It comprises a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Hard carbon micro-spherical composite anode material of lithium battery and preparation method for hard carbon micro-spherical composite anode material
CN102364727A
Preparation method of secondary start-up lithium ion battery cathode material
CN104600309A
Preparation method of soft / hard carbon modified anode material for lithium ion batteries
CN107845810A
Battery negative electrode coating, battery negative electrode sheet and manufacturing method thereof, and lithium ion battery
CN109888200A
Negative electrode material of high-power lithium battery, preparation method and lithium battery
CN111403705A
Cited By
Carbon negative electrode material and preparation method thereof, negative electrode plate, electrochemical device and electronic equipment
CN121553941A